Cardiomyopathy Mutations in Metavinculin Disrupt Regulation of Vinculin-Induced F-Actin Assemblies. Issue 8 (5th April 2019) - Sarker, Muzaddid; Lee, Hyunna T.; Mei, Lin; Krokhotin, Andrey; de los Reyes, Santiago Espinosa; Yen, Laura; Costantini, Lindsey M.; Griffith, Jack; Dokholyan, Nikolay V.; Alushin, Gregory M.; Campbell, Sharon L.
Abstract: Debilitating heart conditions, notably dilated and hypertrophic cardiomyopathies (CMs), are associated with point mutations in metavinculin, a larger isoform of the essential cytoskeletal protein vinculin. Metavinculin is co-expressed with vinculin at sub-stoichiometric ratios in cardiac tissues. CM mutations in the metavinculin tail domain (MVt) occur within the extra 68-residue insert that differentiates it from the vinculin tail domain (Vt). Vt binds actin filaments (F-actin) and promotes vinculin dimerization to bundle F-actin into thick fibers. While MVt binds to F-actin in a similar manner to Vt, MVt is incapable of F-actin bundling and inhibits Vt-mediated F-actin bundling. We performed F-actin co-sedimentation and negative-stain EM experiments to dissect the coordinated roles of metavinculin and vinculin in actin fiber assembly and the effects of three known metavinculin CM mutations. These CM mutants were found to weakly induce the formation of disordered F-actin assemblies. Notably, they fail to inhibit Vt-mediated F-actin bundling and instead promote formation of large assemblies embedded with linear bundles. Computational models of MVt bound to F-actin suggest that MVt undergoes a conformational change licensing the formation of a protruding sub-domain incorporating the insert, which sterically prevents dimerization and bundling of F-actin by Vt. Sub-domain formation is destabilized by CM mutations, disrupting this inhibitory mechanism. These findings provide new mechanistic insights into the ability of metavinculin to tune actin organization by vinculin and suggest that dysregulation of this process by CM mutants could underlie their malfunction in disease. Graphical Abstract: Unlabelled Image Highlights: The cardiac tissue-specific splice isoform of vinculin, metavinculin, negatively regulates vinculin-mediated higher-order F-actin assembly. Metavinculin cardiomyopathy mutants promote disordered F-actin assembly. Computational modeling suggests that actin binding to metavinculin induces a conformational change within the metavinculin-specific insert region and its displaced N-terminus, to form a protruding sub-domain, that prevents dimerization and Vt-induced actin bundling. Cardiomyopathy mutations are predicted to destabilize the protruding sub-domain thereby leading to the loss of metavinculin's regulatory role.